Fit to-organization amplifies unethical pro-organizational behavior - Umama, Hany Azza; Setyawati, Sri Murni; Wulandari, Siti Zulaikha (Institute of Advanced Engineering and Science, 2025)
The study of unethical pro-organizational behavior (UPB) has seen a sharp rise in recent years, with research results explaining that a potential cause of UPB is organizational identification (OI). However, there are inconsistencies in the findings regarding the effect of OI on UPB in the workplace. This study seeks to test the direct effect of OI on UPB, and to explore the mediating role of fit to-organization (Fit-O). To evaluate data collected from employees of micro and small enterprises, this study utilized structural equation modeling-partial least squares (SEM-PLS) analysis, along with the variance accounted for (VAF) method to test the mediation between OI and UPB. The findings confirm that the fit or compatibility of an individual with the organization can strengthen the effect of OI on UPB. The intervening role of Fit-O in the OI-UPB relationship is a crucial theoretical contribution. This research also implies that organizations must balance increasing OI with strong ethical standards to mitigate UPB.